Variations of property (A) constants and Lebesgue-type inequalities for the weak thresholding greedy algorithms - Chu, Hùng Việt (Journal of approximation theory, 2023)
Albiac and Wojtaszczyk introduced property (A) to characterize 1-greedy bases. Later, Dilworth et al. generalized the concept to C-Property (A), where the case C=1 gives property (A). They (among other results) characterized greedy bases by unconditionality and C-property (A). In this paper, we extend the definition of the so-called A-property constant to (A, τ)-property constants and use the extension to obtain new estimates for various Lebesgue parameters. Furthermore, we study the relation among (A, τ)-property constants and other well-known constants when τ varies.